COMBINING SERVQUAL AND IMPORTANCE-PERFORMANCE ANALYSIS TO MEASURE SERVICE QUALITY IN A HOTEL IN TOBRUK, LIBYA: A SUGGESTION FOR PRACTITIONERS - Perdhana, Mirwan Surya; Ahshen, Omelkhair Ali (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2017)
The aim of this study is to present the alternative method in measuring service quality. This study investigates the service quality literatures and introduces the practical method to measure the service quality. To measure service quality, a modified SERVQUAL instrument was distributed towards 100 guest of an international hotel located in Tobruk, Libya. The Importance-Performance Analysis was conducted based on the questionnaire results. Managerial implications and further research opportunities were also discussed.